Materials science and engineering an introduction SI version - Callister,William D.; Rethwisch, David G. (John Wiley & Sons, 2020)
Callister's Materials Science and Engineering: An Introduction, 10th Edition promotes student understanding of the three primary types of materials (metals, ceramics, and polymers) and composites, as well as the relationships that exist between the structural elements of materials and their properties.